KUALIFIKASI KEPENGURUSAN PERSATUAN GURU REPUBLIK INDONESIA (PGRI) GUNA CIPTAKAN GURU PROFESIONAL - Asih, Jayanti Martha Asih; Juniwianto, Gaguk; Rahayu, Puji (Journal of Mandalika Literature, 2023)
An organization must have administrators who certainly have the qualifications to become part of the board. This qualification is very necessary in an organization to create good quality human resources. One of the organizations is PGRI. The Republic of Indonesia Teachers' Association (PGRI) is a place to help create teacher professionalism. This article aims to find PGRI management through qualifications in order to create professional teachers. Being a member or administrator in this PGRI organization must be based on predetermined qualifications. The qualifications in question are the qualifications contained in the AD/ART that have been determined, either general or special qualifications. With the provisions stipulated in the PGRI management, the aim is to obtain good quality management members. In a management there is a structure that will help administrators carry out their duties and coordinate well. This will affect the management and management of the PGRI organization. In addition to management qualifications, PGRI also has levels that will later work together to achieve common goals. one effects of good management is to help realize the goal of creating professional teachers. Teacher professionalism referred to here is a teacher who has commitment, skills and knowledge as well as a good attitude that sets a good role model for students. Where these professional teachers contribute to help improve the quality of education in Indonesia.